2005
DOI: 10.1002/ange.200461632
|View full text |Cite
|
Sign up to set email alerts
|

cis‐Bromierung von Alkinen ohne kationische Zwischenstufen

Abstract: Professor Herbert Meier zum 65. Geburtstag gewidmetDer Lehrbuchmechanismus der trans-Bromierung von Alkenen und Alkinen über ein mehr oder weniger symmetrisches cyclisches Bromonium-Ion trifft nicht immer zu -schon beim Stammsystem, der Reaktion von Brom mit Ethylen, ist der Mechanismus vermutlich falsch. Hochreines Brom reagiert mit Ethylen in wasserfreiem Dichlormethan bei Raumtemperatur extrem langsam. Entsprechende Lösungen sind bis zu mehrere Tage vollkommen stabil. Erst Lichteinwirkung oder Spuren von Sä… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…This was confirmed by both experimental and calculated data for C 2 H 2 (1a). 10, 16 Herges et al have found that three different types of such complexes derived from 1a may exist. 16 We have optimized the structures of 1-2Br 2 π-complexes and found only one type of structure as local minima.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This was confirmed by both experimental and calculated data for C 2 H 2 (1a). 10, 16 Herges et al have found that three different types of such complexes derived from 1a may exist. 16 We have optimized the structures of 1-2Br 2 π-complexes and found only one type of structure as local minima.…”
Section: Resultsmentioning
confidence: 99%
“…10, 16 Herges et al have found that three different types of such complexes derived from 1a may exist. 16 We have optimized the structures of 1-2Br 2 π-complexes and found only one type of structure as local minima. The general view of these complexes (π-C-II) is shown in Figure 10.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations